Pediatric lymphoma patients in Malawi present with poor health‐related quality of life at diagnosis and improve throughout treatment and follow‐up across all Pediatric PROMIS‐25 domains. Issue 10 (2nd August 2021) - Ellis, Grace K.; Chapman, Hutton; Manda, Agness; Salima, Ande; Itimu, Salama; Banda, Grace; Seguin, Ryan; Manda, Geoffrey; Butia, Mercy; Huibers, Minke; Ozuah, Nmazuo; Tilly, Alyssa; et al.
Abstract: Background: Patient‐reportedoutcomes (PROs) that assess health‐related quality of life (HRQoL) are increasingly important components of cancer care and research that are infrequently used in sub‐Saharan Africa (SSA). Methods: We administered the Chichewa Pediatric Patient‐Reported Outcome Measurement Information System Pediatric (PROMIS)‐25 at diagnosis, active treatment, and follow‐up among pediatric lymphoma patients in Lilongwe, Malawi. Mean scores were calculated for the six PROMIS‐25 HRQoL domains (Mobility, Anxiety, Depressive Symptoms, Fatigue, Peer Relationships, Pain Interference). Differences in HRQoL throughout treatment were compared using the minimally important difference (MID) and an ANOVA analysis. Kaplan–Meier survival estimates and Cox hazard ratios for mortality are reported. Results: Seventy‐five children completed PROMIS‐25 surveys at diagnosis, 35 (47%) during active treatment, and 24 (32%) at follow‐up. The majority of patients died ( n = 37, 49%) or were lost to follow‐up ( n = 6, 8%). Most ( n = 51, 68%) were male, median age was 10 (interquartile range [IQR] 8–12), 48/73 (66%) presented with advanced stage III/IV, 61 (81%) were diagnosed with Burkitt lymphoma and 14 (19%) Hodgkin lymphoma. At diagnosis, HRQoL was poor across all domains, except for Peer Relationships. Improvements in HRQoL during active treatment and follow‐up exceeded the MID. On exploratory analysis, fair‐poor PROMIS Mobility <40 and severe Pain Intensity = 10 at diagnosis were associated with increased mortality risk and worse survival, but were not statistically significant. Conclusions: Pediatric lymphoma patients in Malawi present with poor HRQoL that improves throughout treatment and survivorship. Baseline PROMIS scores may provide important prognostic information. PROs offer an opportunity to include patient voices and prioritize holistic patient‐centered care in low‐resource settings.